2005
DOI: 10.1002/cne.20826
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‐α distribution in male rodents is associated with social organization

Abstract: It has been hypothesized that site-specific reduction of estrogen receptor-alpha (ERalpha) is associated with the expression of male prosocial behaviors. Specifically, highly social males are predicted to express significantly lower levels of ERalpha than females and less social males in brain regions associated with prosocial behavior including the bed nucleus of the stria terminalis (BST) and the medial amygdala (MeA). This hypothesis was tested by comparing ERalpha immunoreactivity (IR) in three species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 80 publications
(97 reference statements)
5
66
3
2
Order By: Relevance
“…Brain distribution of estrogen receptors (ER) and oxytocin receptors (OTR) may be particularly important for differences in social behaviors. ER-α density appears to be associated with social organization in male rodents (Cushing and Wynne-Edwards, 2006), and ER expression is associated with photoperiod dependent changes in aggressive behavior in Peromyscus (Trainor et al 2007). In meadow voles, OTR binding is higher in the lateral septum, central amygdala, and lateral amygdala of naïve SD females than LD females (Parker et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Brain distribution of estrogen receptors (ER) and oxytocin receptors (OTR) may be particularly important for differences in social behaviors. ER-α density appears to be associated with social organization in male rodents (Cushing and Wynne-Edwards, 2006), and ER expression is associated with photoperiod dependent changes in aggressive behavior in Peromyscus (Trainor et al 2007). In meadow voles, OTR binding is higher in the lateral septum, central amygdala, and lateral amygdala of naïve SD females than LD females (Parker et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In prairie voles, dopamine, oxytocin, and vasopressin act within the mesolimbic reward pathway to establish pair bonds between mates [30]. Across Microtus vole species, differences in the distribution of oxytocin and vasopressin receptors as well as estrogen receptor a are associated with species differences in mating strategy [97,98], and studies that investigate the consequences of these variations in field settings have been conducted [99,100]. Work in seasonally social meadow voles as well as in colonial South American rodents has suggested parallel and potentially convergent pathways by which oxytocin receptor density is involved in natural variation in affiliative behavior and group living outside the context of monogamy [78].…”
Section: Internal Attributes: Life-history Traitsmentioning
confidence: 99%
“…Thus, the present results are not surprising. There is evidence that estrogen increases aggression and decreases affiliation through ERa (Ogawa et al 1997;Rissman et al 1999;Scordalakes & Rissman 2004), and low levels of ERα in the anterior hypothalamus (AHA), MeA and BNST were associated with the effect of estrogen on aggression in monogamous California mice (Peromyscus californicus Gambel, 1848) (Cushing & Wynne-Edwards 2006;Trainor et al 2008). However, another report suggested that the MeA is not involved in mediating changes in individual levels of aggression in female California mice (Davis & Marler 2004).…”
Section: Effects Of Ovariectomy On Female Mandarin Volesmentioning
confidence: 99%
“…Decreased and eliminated ERα is associated with decreased aggression (Ogawa et al 1998;Cushing & Wynne-Edwards 2006;Trainor et al 2006b). Furthermore, neurobiological data suggest that estrogen may facilitate drug taking by interacting with reward-and stress-related systems (Anker & Carroll 2011).…”
Section: Introductionmentioning
confidence: 99%